Using tuberous sclerosis complex to understand the impact of MTORC1 signaling on mitochondrial dynamics and mitophagy in neurons - Ebrahimi-Fakhari, Darius; Saffari, Afshin; Wahlster, Lara (Autophagy, 2017)
Constitutive activation of the MTOR pathway is a key feature of defects in the tuberous sclerosis complex and other genetic neurodevelopmental diseases, collectively referred to as MTORopathies. MTORC1 hyperactivity promotes anabolic cell functions such as protein synthesis, yet at the same time catabolic processes such as macroautophagy/autophagy are suppressed. Mitochondria are major substrates of autophagy; however, their role in MTORopathies remains largely undefined. Here, we review our recent study showing that several aspects of mitochondrial function, dynamics and turnover are critically impaired in neuronal models of TSC. We discuss the relevance of these findings to neurological manifestations associated with TSC and speculate on autophagy as a novel treatment target for MTORopathies.